Analisis Model Pembelajaran Fiqih Di MTs Aisyiyah Binjai - Tanjung, Aisyah Rahma Fitri (Educate: Jurnal Ilmu Pendidikan dan Pengajaran, 2023)
This research was conducted to determine the learning of Fiqh on the Slaughter of Sacrificial Animals and Akikah using the Discovery Learning learning model. The results show that the discovery learning model is very effective. This can be seen from the increase in student learning outcomes, namely by using the discovery learning learning model, because in the learning process using the discovery learning learning model students are actively involved in learning and train students' critical thinking skills so that students are able to find problems given by the teacher. Tests are given to students in each cycle.